Respuesta :

Answer:

x = 9 and y = 1

Step-by-step explanation:

Here,

x = 10 - y and y = x - 8 is given

then, name the equation

x = 10 - y ...(1)

y = x - 8 ...(2)

Now, put the value of x in equation (2) we get

y = x - 8

y = (10 - y) - 8

y = 10 - y - 8

y + y = 10 - 8

2y = 2

y = 2÷2

y = 1

Here, we get the value of y = 1

Now, we put the value of y in equation (1) we get

x = 10 - y

x = 10 - (1)

x = 10 - 1

x = 9

VERIFICATION:

x = 10 - y

9 = 10 - 1

9 = 9

Hence, LHS = RHS

-TheUnknownScientist

ACCESS MORE